The effect of finasteride and dutasteride on the growth of wpe1-na22 prostate cancer xenografts in nude mice - Opoku-Acheampong, Alexander Boadu (Kansas State University, 2011)
5α-reductase 1 (5αR1) and 5α-reductase 2 (5αR2) convert testosterone into the more potent androgen, dihydrotestosterone (DHT), that is responsible for regulating prostate growth and proliferation. 5αR2 is the main isoenzyme in normal prostate tissue, however prostate tumors have increased 5αR1 and decreased or unchanged 5αR2 expression. Previously, finasteride (5αR2 inhibitor) treatment begun 3 weeks after tumor implantation had no effect on Dunning R3327-H rat prostate tumor growth. We believe the tumor compensated for finasteride treatment by increasing tumor 5αR1 activity to produce dihydrotestosterone to stimulate its growth. We hypothesize that finasteride treatment would not significantly alter tumor growth even if begun before tumor implantation, while dutasteride (dual 5αR1 & 5αR2 inhibitor) treatment would decrease tumor growth regardless if treatment is begun before or after tumor implantation. Sixty, 8-week old male nude mice were randomized to Control, Pre-Finasteride, Post-Finasteride, Pre-Dutasteride and Post-Dutasteride diet groups (all diets contained 83.3 mg drug/kg diet). Pre groups began their treatment diets 1-2 weeks prior to tumor implantation, while post groups began their treatment diets 3 weeks after tumor implantation. Tumors were implanted by subcutaneous injection of 1 x 10⁵ WPE1-NA22 human prostate cancer cells in Matrigel™ and allowed to grow for 22 weeks. Tumor areas, body weights, and feed intakes were measured weekly. At study conclusion, prostate and seminal vesicle weights were significantly decreased in all treatment groups versus the control. Dutasteride intake also significantly reduced seminal vesicle weights compared to finasteride intake. There were no significant differences in final tumor areas or tumor weights between groups, likely due to poor tumor growth. In follow-up studies, proliferation of WPE1-NA22 prostate cancer cells, and its parent line RWPE-1 prostate epithelial cells, were unaltered by treatment with testosterone, DHT, or the synthetic androgen mibolerone, suggesting that these cell lines are not androgen-sensitive. Thus, the lack of response to androgen treatment by WPE1-NA22 prostate cancer cells may explain the inadequate tumor growth observed.
Keywords: Prostate cancer; Androgens; Finasteride; Dutasteride; 5α-reductase; WPE1-NA22; Nutrition (0570)